Possibilities to compare graffiti with handwriting - Brandner, Walter (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
From the forensic point of view it is not easy to identify a person as an author of writing in graffiti mode, but at least in some cases it seems to be possible.
Keywords: graffiti; forensic examination of handwriting